Studies on the biocompatibility of bacterial cellulose. - Alexandre, Nuno (2013)
Bacterial cellulose was functionalized with a chimeric protein containing a cellulose-binding module and the adhesion peptide Arg-Gly-Asp. Small-diameter bacterial cellulose membranes were produced and subcutaneously implanted in sheep for 1–32 weeks. The implants triggered a biological response similar to other high surface-to-volume implants. There were no significant differences in the inflammation degree between the bacterial cellulose coated with the recombinant protein Arg-Gly-Asp–cellulosebinding module and the native bacterial cellulose. The implants were considered to be mildly irritating to the tissue compared to the negative control sample (expanded polytetrafluoroethylene). The analysis of the fluorescence microscopy revealed that, apart from increasing cell adhesion, the presence of Arg-Gly-Asp stimulated an even cell distribution, while the cells on the untreated bacterial cellulose seemed to form aggregates. Furthermore, the cells on the Arg-Gly-Asp–treated bacterial cellulose presented a more elongated morphology. Mechanical tests indicated that the small-diameter bacterial cellulose tubes were more elastic than the human arteries and veins.